KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA DIKAJI DARI SIKAP ILMIAH DI SMA - Putri Sholehah Hasanah; Bistari Bistari; Dian Ahmad BS (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe and analyze the students' mathematical understanding ability in solving story problems studied from the scientific attitude on the material of sequences and series in class XI IPA 3 SMA Negeri 9 Pontianak. This research is a qualitative descriptive study. Data on students' mathematical understanding abilities were collected through tests and interviews. Data on students' scientific attitudes were collected through observation and interviews. The data sources were three students of class XI IPA 3 of SMA Negeri 9 Pontianak in the academic year 2021/2022 who were chosen as research subjects, namely: one student with the ability to understand mathematically on indicators of translation, interpretation and extrapolation. The results showed: 1) students' mathematical understanding ability in the medium category translation indicator had a scientific attitude including the sufficient category; 2) students' mathematical understanding ability in the medium category interpretation indicator has a scientific attitude including the sufficient category; 3) students' mathematical understanding ability in the low category extrapolation indicator has a scientific attitude including the unfavorable category.